Kaposi's sarcoma-associated herpesvirus gH/gL: glycoprotein export and interaction with cellular receptors. - Hahn, Alexander; Birkmann, Alexander; Wies, Effi; Dorer, Dominik; Mahr, Kerstin; Stürzl, Michael; Titgemeyer, Fritz; Neipel, Frank (Journal of Virology, 2009)
The attachment, entry, and fusion of Kaposi's sarcoma-associated herpesvirus (KSHV) with target cells are mediated by complex machinery containing, among others, viral glycoprotein H (gH) and its alleged chaperone, gL. We observed that KSHV gH, in contrast to its homologues in several other herpesviruses, is transported to the cytoplasm membrane independently from gL, but not vice versa. Mutational analysis revealed that the N terminus of gH is sufficient for gL interaction. However, the entire extracellular part of gH is required for efficient gL secretion. The soluble ectodomain of gH was sufficient to interact with the surfaces of potential target cells in a heparin-dependent manner, and binding was further enhanced by coexpression of gL. Surface plasmon resonance revealed a remarkably high affinity of gH for glycosaminoglycans. Heparan sulfate (HS) proteoglycans of the syndecan family act as cellular receptors for the gH/gL complex. They promoted KSHV infection, and expression of gH/gL on target cells inhibited subsequent KSHV infection. Whereas gH alone was able to bind to HS, we observed that only the gH/gL complex adhered to heparan sulfate-negative cells at lamellipodium-like structures.